2017
DOI: 10.1136/bmjsem-2016-000175
|View full text |Cite
|
Sign up to set email alerts
|

Ankle syndesmosis repair and rehabilitation in professional rugby league players: a case series report

Abstract: Background/aimThe distal tibiofibular joint is described as a syndesmosis. Traditionally, severe syndesmotic injuries with diastasis have been treated surgically with screw fixation. This case series details an ankle syndesmosis tightrope repair and an accelerated rehabilitation protocol that reduces the amount of time to return to professional rugby league in the UK. The aim of this study was to describe players’ journey from injury, through diagnosis to surgery, rehabilitation and return to participation, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 33 publications
0
31
0
3
Order By: Relevance
“…Hunt et al [10] suggested 70-84 days is the likely RTP time frame with their preferred method of suture button fixation. Alex Latham [11] in his case series suggested return to sport is possible within 61 days following syndesmosis injury, provided surgery with tightrope and rehabilitation is uncomplicated.…”
Section: Discussionmentioning
confidence: 99%
“…Hunt et al [10] suggested 70-84 days is the likely RTP time frame with their preferred method of suture button fixation. Alex Latham [11] in his case series suggested return to sport is possible within 61 days following syndesmosis injury, provided surgery with tightrope and rehabilitation is uncomplicated.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence to suggest that the burden from high ankle sprains is greater than previously thought, with incidence quoted as high as 18% of all ankle sprains and result in greater levels of pain, treatment and lost sports time than lateral sprains. 15 The syndesmosis consists of a complex of anterior inferior tibiofibular ligament (AITFL), the posterior inferior tibiofibular ligament (PITFL), the interosseous ligament and the transverse tibiofibular ligament. Mechanism of injury is usually internal rotation of the leg with forced external rotation of the talus and foot.…”
Section: Syndesmosis Injuriesmentioning
confidence: 99%
“…Von den 11 eingeschlossenen Studien lieferten nur Lin et al [14], Pajaczkowski [15] und Knapik et al [19] eine genaue Einteilung der Schweregrade der Verletzung. Dies muss kritisch betrachtet werden, da die anderen Arbeiten bei der Einordnung des Verletzungsgrades nicht auf die standardisierte Klassifikation der Syndesmosenverletzung verwiesen, sondern allgemeine Formulierungen wie "leicht", "mittel" und "schwer" verwendeten [18] [27]. Dadurch lassen sich die Rehabilitationsprotokolle nicht im direkten Vergleich gegenüberstellen, da die Interventionsgruppen nicht einheitlich zusammengefasst werden können.…”
Section: Diskussionunclassified